Evaluasi Kedalaman Fondasi Tiang Pancang terhadap Beban Maksimum atau Distribusi Beban (Study Kasus Pembangunan Rumah Kos 4 Lantai Jl. Siwalankerto Timur /8) - Gati Sri Utami; Mega Kartika Sari R; Mila Kusumawardani; Arintha Indah DS; Theresia MCA (Jurnal Teknik Sipil, 2023)
The foundation is part of an engineering system that transmits the working load and self-weight into the soil or rock. The construction of a 4-storey boarding house with a land area of 1000mÂ² located on Jalan Siwalankerto Timur II/8 Surabaya has been planned using a bore pile foundation with a diameter of 40 cm and a depth of 13m. This study re-planned the initial design of the foundation with pile foundations based on the analysis of the forces in the auxiliary program structure. The purpose of re-planning is to determine the depth of the pile foundation according to the load distribution received by each pile in a group.Based on the analysis of the bearing capacity of the pile foundation using the Mayerhoff method and the structural analysis of the auxiliary program, the results obtained are the bearing capacity of the pile foundation with a diameter of 40 cm, the deeper the value increases. Foundation depth based on maximum load and load distribution is 12m, because it is only influenced by axial loads and not affected by moments that occur based on the results of structural analysis, because the values are small (0.6% and 4.4%) compared to axial loads